The SAMI Galaxy Survey: stellar population and structural trends across the Fundamental Plane. Issue 4 (23rd April 2021) - D'Eugenio, Francesco; Colless, Matthew; Scott, Nicholas; van der Wel, Arjen; Davies, Roger L; van de Sande, Jesse; Sweet, Sarah M; Oh, Sree; Groves, Brent; Sharp, Rob; Owers, Matt S; Bland-Hawthorn, Joss; et al.
ABSTRACT: We study the Fundamental Plane (FP) for a volume- and luminosity-limited sample of 560 early-type galaxies from the SAMI survey. Using r -band sizes and luminosities from new multi-Gaussian expansion photometric measurements, and treating luminosity as the dependent variable, the FP has coefficients a = 1.294 ± 0.039, b = 0.912 ± 0.025, and zero-point c = 7.067 ± 0.078. We leverage the high signal-to-noise ratio of SAMI integral field spectroscopy, to determine how structural and stellar population observables affect the scatter about the FP. The FP residuals correlate most strongly (8σ significance) with luminosity-weighted simple stellar population (SSP) age. In contrast, the structural observables surface mass density, rotation-to-dispersion ratio, Sérsic index, and projected shape all show little or no significant correlation. We connect the FP residuals to the empirical relation between age (or stellar mass-to-light ratio Υ ⋆ ) and surface mass density, the best predictor of SSP age amongst parameters based on FP observables. We show that the FP residuals (anti)correlate with the residuals of the relation between surface density and Υ ⋆ . This correlation implies that part of the FP scatter is due to the broad age and Υ ⋆ distribution at any given surface mass density. Using virial mass and Υ ⋆, we construct a simulated FP and compare it to the observed FP. We find that, while the empirical relations between observed stellar population relations and FP observables are responsible for most (75 per cent) of the FP scatter, on their own they do not explain the observed tilt of the FP away from the virial plane.